Analyses of Chinese manufacturing entrepreneurs' business performance improvement through entrepreneurial orientation - Hu Mengting; Noor Fzlinda Fabeil; Ang, Hong Loong (Human Resource Management Academic Research Society, 2024)
This study delves deeply into the intricate mechanism by which Chinese manufacturing enterprises enhance their entrepreneurial orientation through the strategic implementation of information sharing, ultimately fostering an environment that is conducive to improving profitability and overall business progress. By leveraging network capabilities, fostering interorganizational learning, and harnessing network power, these enterprises can effectively achieve resource integration, facilitate seamless knowledge sharing and synergies, promote market adaptation and innovation, and ultimately enhance their competitive edge in the global marketplace. The empirical analysis conducted underscores the significant role of information sharing in bolstering the entrepreneurial orientation of enterprises, enabling them to secure distinct advantages in the fiercely competitive market landscape, foster sustainable growth, and attain a comprehensive improvement in overall enterprise performance.